Influence of environmental conditions on spawn run, pin head formation and biological efficiency of Pleuratus djamar - SHARMA, B. BHOOSHAN (Indian Phytopathology, 2005)
The effect of prevailing environmental conditions on spawn run, pin head formation and biological efficiency of Pleurotus djamor was studied continuously for 9 months from February-October 2003 on Paddy, Wheat and Mustard straw. July month took minimum time (6.75 to 8.5 days) for spawn run and 10.5 to 11.5 days for pin head formation and gave the highest biological efficiency (45.2 to 46.0) on all the three substrates. However, February and March months took more period for spawn run and pin head initiation and yield was less .No spawn run was observed in months of April, May and June. Correlation coefficient analysis showed negative correlation with maximum, minimum and average temperature. It was negative and significant only for the period for spawn run and pin head formation in case of wheat and mustard substrates. Correlation coefficient for biological efficiency was negative and non- significant with maximum, minimum and average temperature in case of paddy and wheat straw substrate, however, mustard straw showed positive and nonsignificant relationship with minimum temperature.